UTILIZATION OF PLANT PROTEINS IN FUNCTIONAL NUTRITION - V. G. Kulakov; S. V. Kapustin (Овощи России, 2018)
Development of functional food products technology is considered to be a prospect way for creating new food products. Such products are known to be popular among consumers. Utilization of plant proteins allows to widen and improve food assortment and quality. The article represents a review of plant proteins utilization in production of functional food. For optimization of flour confectionery chemical composition the authors utilized a method of receipts modeling. Simulation of combined products is based on the principles of food combinatorics and aims to create recipes of new types of food products on basis of methods of mathematical optimization by reasonable selection of the basic raw materials, ingredients, food additives and dietary supplements, totality of which ensures formation desired organoleptic, physical and chemical properties product as well as a predetermined level of food, biological and energy value. Modeling process of combined products recipes includes the following three stages: preparation of input data for the design, formalization requirements for the composition and properties of raw ingredients and quality final product, process modeling; product design with desired structural properties.